Does Short and Long Run Equilibrium Exists Between Electricity Consumption and Foreign Aid - Dhungel, Kamal Raj (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Because of its limited and unmanaged internal resources to promote socio-economic development, Nepal has become an aid-dependent country. Past trends show that the majority of extant hydropower projects in Nepal were built through aid. In this light, using a single equation model, this study attempts to investigate short and long run equilibrium between two variables constructed from data collected between 1974-2011: 1) electricity consumption as the dependent variable, and 2) foreign aid as explanatory variable. There are two co-integrating equations that indicate a long run equilibrium between the variables. The long run elasticity coefficient reveals that a 1% change in foreign aid will change the electricity consumption by 0.48%. The results of ECM indicate that there is both short and long run equilibrium in the system. The coefficient of one period lag residual is negative and significant which represents the long run equilibrium. The coefficient is -0.336, which means that the system corrects its previous period disequilibrium at a speed of 33.6% annually. DOI: http://dx.doi.org/10.3126/hn.v15i0.11293 HYDRO Nepal Journal Journal of Water, Energy and Environment Volume: 15, 2014, July Page: 48-52